2014
DOI: 10.2527/jas.2013-7209
|View full text |Cite
|
Sign up to set email alerts
|

TRIENNIAL GROWTH SYMPOSIUM— Effects of dietary 25-hydroxycholecalciferol and cholecalciferol on blood vitamin D and mineral status, bone turnover, milk composition, and reproductive performance of sows12

Abstract: To evaluate the role of vitamin D3 during gestation and lactation of sows, 2 independent experiments were performed with the aim of investigating sow reproductive performance, milk composition (study 1 only), and changes in blood status of 25-hydroxycholecalciferol (25-OH-D3), 1,25-dihydroxycholecalciferol (1,25-(OH)2-D3; study 2 only), minerals, and bone markers of sows during gestation and lactation. Study 1 comprised 39 primi- and multiparous crossbred sows fed 1 of 3 barley meal-based diets fortified with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 28 publications
6
56
2
1
Order By: Relevance
“…Interestingly, in the study herein, maternal vitamin D influenced postweaning growth but not in the way that we had hypothesized on the basis of previous conclusions drawn from Hines et al (2013) and Weber et al (2014). In the current study, it appeared that the only consistent impact on growth performance was that pigs from sows fed 2,000 IU of vitamin D 3 /kg had increased ADG and ADFI in the nursery and improved ADG and G:F in finishing.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Interestingly, in the study herein, maternal vitamin D influenced postweaning growth but not in the way that we had hypothesized on the basis of previous conclusions drawn from Hines et al (2013) and Weber et al (2014). In the current study, it appeared that the only consistent impact on growth performance was that pigs from sows fed 2,000 IU of vitamin D 3 /kg had increased ADG and ADFI in the nursery and improved ADG and G:F in finishing.…”
Section: Discussionsupporting
confidence: 44%
“…These alterations would suggest the potential for increased postnatal growth performance. Weber et al (2014) observed increases in piglet BW at birth and weaning in piglets from dams supplemented 50 µg of 25(OH)D 3 /kg compared with piglets from dams supplemented 2,000 IU of vitamin D 3 /kg. However, no previous research has evaluated whether pigs from dams supplemented varying forms or concentrations of vitamin D have improved postnatal growth after weaning or the impacts of maternal vitamin D on carcass characteristics.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This suggests that a portion of the vitamin D 3 that is absorbed may be stored in adipose tissue rather than being transported to the liver for hydroxylation. The serum 25(OH) D 3 concentrations achieved in gestation from supplementing 25(OH)D 3 were less than those in the reports of previous researchers (Lauridsen et al, 2010;Coffey et al, 2012;Weber et al, 2014); this may be due to the time of sampling and duration of feeding, which Weber et al (2014) 1 In total 112 sows and litters were used to determine the effects of supplemental vitamin D from varying levels of vitamin D 3 or from synthetic 25(OH) D 3 on maternal performance, subsequent pig performance, sow and piglet serum vitamin metabolites, neonatal bone mineralization, and piglet muscle development. Means represent the average serum metabolite from 48 randomly selected litters (2 pigs per litter were bled for serum analysis) within treatments, and the same litters within each day were analyzed.…”
Section: Sow Serum 25(oh)d 3 Vitamin D 3 α-Tocopherol and Retinolcontrasting
confidence: 51%
“…Prior to receiving their daily meal, sows were bled on d 0 and 30 of the trial via jugular venipuncture to collect serum for 25(OH)D 3 analysis. Results from this study were then used to develop a prediction equation to determine the dietary vitamin D 3 concentration needed to achieve a serum 25(OH)D 3 response in gestating sows similar to levels previously reported in the literature (Weber et al, 2014) for females fed 50 µg of 25(OH)D 3 /kg of complete diet as their sole source of vitamin D.…”
Section: Animals Diets and Treatment Designmentioning
confidence: 99%